Of rajuk, durhaka and demasculinization. Examining class inequality and gender representations in Hussain Haniffs Hang Jebat (1961) - Muhamad Farid Abdul Rahman (Tanjong Malim, 2020)
Of rajuk, durhaka and demasculinization. Examining class inequality and gender representations in Hussain Haniffs Hang Jebat (1961) by Muhamad Farid Abdul Rahman